PENGEMBANGAN MEDIA PEMBELAJARAN BOLA BASKET BERBASIS VIDEO ANIMASI UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Tania Ika Putri; Eka Supriatna; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to develop new innovations in the form of video-based animation learning media that can add effectiveness to the learning process, especially basketball material at the junior high school level. This research is research and development (R & D). This study uses the ADDIE development method with several steps, namely: analysis, design, development, implementation and evaluation. The subjects of the trial in this study were Pontianak 10 Public High School, Pontianak 24 Public Middle School and Sungai Raya 2 Public Middle School. The results of the study were DVD (Digital Versatile Disk) interactive learning that had been validated and tested. The results of the validation by material experts got the category "very valid" with a value of 90% and the assessment by media experts got a value of 83.3% with the category "very valid". The results of the effectiveness tests in three schools showed a percentage increase in value of 25.45% in Pontianak 10 Public Junior High School, 25.45% in Pontianak Pontianak Public High School and 19.03% in Sungai Raya 2 Public Middle School. The feasibility test was also conducted with the results of 90.76% in Pontianak 10 Public Junior High School, 87.96% in Pontianak 24 Public Middle School and 84.76% in Sungai Raya 2 Public Middle School. So it can be concluded that basketball video-based learning media products that are developed valid, feasible and effective are used in the learning process in school. Keywords : Animated Video, Basketball, Instructional Media